Aplicación De Auditoría Financiera Al Gobierno Autónomo Descentralizado Parroquial De Chantaco, Periodo Enero – Diciembre 2012 - Pucha Sinche, Wilber Antonio (2016)
The investigation work is related with the execution of a denominated audit “APPLICATION OF FINANCIAL AUDIT TO THE PAROCHIAL DECENTRALIZED AUTONOMOUS GOVERNMENT DE CHANTACO, PERIOD JANUARY-DECEMBER 2012” whose objectives are guided to determine the execution of the legal dispositions on the part of authorities and employees, of the GAD. Parochial of Chantaco. To analyze and to evaluate the procedures carried out in the handling of financial activities of the bills, to determine if the procedures are correct and reliable, to Emit a Report that contains comments conclusions and recommendations that it allows the appropriate and opportune taking of decisions, for the execution of the goals and objectives for those that the Parochial Institution was created. Presently work was made use of the used methodology that recommends that is to say in the manual of financial audit of the general controllership of the state he/she has a managerial focus whose results are expressed in the evaluation of the system of internal control implanted in the entity, the same one that presents deficiencies like, the bad presentation and execution of the bank reconciliations, segregation of functions doesn't exist and reconciliations of balances don't exist especially with those bigger than accounting in the fixed assets, lack of analysis reconciliation of average balances of the passive ones and on the other hand physical verifications of the goods of long duration don't exist. As for the the balances in the states financier that are presented settles down that it is acceptable the grade of execution of the effective legal dispositions in the development of the countable and financial activities of the entity in the period that was analyzed. for example he/she settled down that exists in the balances of the average asset of USD 104,547.76 that it is reasonable; the reconciled balance of active fixed it was of USD 8,115.44 and for revaluation of active fixed for USD 8,514.44 what deserved an adjustment seat for their implementation in the financial states of the entity, finally the analysis of the movement of the bill passive current was determined that the balance according to assistants is of USD 4,088.67 that it doesn't coincide with the balance of the financial states, existing a error in the month of October for the quantity of USD 254.12 for what intends an adjustment. In the GAD Parish of Chantaco the analyzed period has not proceeded to carry out the upgrade of the values of the goods of long duration, the same ones that are registered at historical cost, neither he/she has taken into the account the depreciation of such goods, the conclusions and recommendations were formulated of which the most important have that the system of implemented internal control enjoys little dependability since they were deficiencies that are consisted in the audit report, because the directive and officials, they have not observed relating legal and regulation dispositions to the control and handling of the public resources and its recommendation that the directive, especially to the president like responsible for the internal control, it will welcome the recommendations pointed out in the audit report, that is to say he/she will improve the financial internal control of the entity with the purpose of having reliable information for the taking of decisions.